HTERT promotes the invasion of gastric cancer cells by enhancing FOXO3a ubiquitination and subsequent ITGB1 upregulation. Issue 1 (14th September 2015) - Hu, Changjiang; Ni, Zhenghong; Li, Bo-sheng; Yong, Xin; Yang, Xin; Zhang, Jian-wei; Zhang, Dan; Qin, Yong; Jie, Meng-meng; Dong, Hui; Li, Song; He, Fengtian; et al.
Abstract : Background and aims: Human telomerase reverse transcriptase (hTERT) plays an important role in cancer invasion, but the relevant mechanism is not well known. This study aims to investigate the role and mechanism of hTERT in gastric cancer metastasis. Design: Proteomics analysis, qPCR and western blotting were used to screen for hTERT-regulated candidate molecules in gastric cancer invasion. Chromatin immunoprecipitation (ChIP) qPCR was performed to identify the binding sites of hTERT at the regulatory region of the integrin β1 ( ITGB1 ) gene. ChIP assays were further applied to elucidate the transcription factors that bound to the regulatory region. The interactions between hTERT and the transcription factors were tested by co-immunoprecipitation (Co-IP) and glutathione S-transferase (GST) pull-down experiments. Moreover, the revealed pathway was verified in tumour-bearing nude mice and human gastric cancer tissues. Results: ITGB1 was identified as a downstream gene of hTERT, and there were two hTERT-binding regions within this gene. hTERT alleviated the binding of forkhead box O3 (FOXO3a) to FOXO3a binding element (+9972∼+9978), but it enhanced the binding of forkhead box M1 (FOXM1) to FOXM1 binding element (−1104∼−1109) in ITGB1 gene. Importantly, FOXO3a played a major role in hTERT-induced ITGB1 expression, and the hTERT/murine double minute 2 (MDM2) complex promoted the ubiquitin-mediated degradation of FOXO3a. Moreover, hTERT increased ITGB1 expression in xenograft gastric cancer, and the level of hTERT was positively correlated with that of ITGB1 in human gastric cancer tissues. Conclusions: The hTERT/MDM2–FOXO3a–ITGB1 pathway markedly contributes to hTERT-promoted gastric cancer invasion, suggesting that this pathway might be a novel target for the prevention and treatment of gastric cancer metastasis.